2023
DOI: 10.3389/fpubh.2022.978237
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the Barthel Index for mortality in patients with COVID-19: A cross-sectional study

Abstract: ObjectiveThis study aimed to analyze the association between the activity of daily living (ADL), coronavirus disease (COVID-19), and the value of the Barthel Index in predicting the prognosis of patients.MethodsThis study included 398 patients with COVID-19, whose ADL at admission to hospital were assessed with the Barthel Index. The relationship between the index and the mortality risk of the patients was analyzed. Several regression models and a decision tree were established to evaluate the prognostic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…It has been shown that the Barthel's index has a prognostic value for mortality in COVID-19 patients and ADL dependence is significantly related to mortality. 28,29 To the authors' knowledge, there is no published local data on post-COVID discharge ER consultation, readmission, and mortality. However, there was a similar study done by Kingery et al in a quaternary referral hospital in New York City.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the Barthel's index has a prognostic value for mortality in COVID-19 patients and ADL dependence is significantly related to mortality. 28,29 To the authors' knowledge, there is no published local data on post-COVID discharge ER consultation, readmission, and mortality. However, there was a similar study done by Kingery et al in a quaternary referral hospital in New York City.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic tests were collected in the nursing homes, and nasopharyngeal swabs were sent to the reference laboratory (Hospital Universitario Ramón y Cajal) for PCR analysis. In residents, geriatric assessments, including Barthel scores for activities of daily living [ 24 ] and the Spanish-validated version of the MiniMental State exam, Lobo-MMT for cognitive function assessment [ 25 ], were performed. All participants were informed of the results of all tests, but personal data were anonymized for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…By assigning scores to each element and summarizing these scores, the BI is derived, ranging from 0 to 100. A higher BI score indicates greater autonomy and proficiency in performing daily life activities (6,(25)(26)(27).…”
Section: Study Population 23 Assessment Of Adlmentioning
confidence: 99%